Corporate Social Responsibility in the Banking Sector of Bangladesh: A Case Study on AB Bank Limited (Global Journal of Management and Business Research, 2015)
The aim of our article is to scrutinize the practices of corporate social responsibility (CSR) of AB Bank in Bangladesh as well as give some suggestions based on findings. The study found that total CSR expenditure of AB bank has been increasing over the years but the growth rate of total CSR expenditure is seen decreasing trend. The study also found that growth rate of CSR expenditure on education and environment sector decreased in 2013 compared to the previous years. So for the wellbeing of the society CSR expenditure of AB Bank should increase much more. This study further found that the CSR practices of Bangladesh are confined within some selected sectors. Therefore this study suggests some possible areas should be considered for CSR activities. This Study further suggests that a proper guideline by Government regarding CSR contribution, involvement of large corporation in CSR activities and mandating CSR disclosures in the annual report will fulfill the intended goals of the corporate organizations and also ensure a successful and sustainable development of the society.
Keywords: corporate social responsibility (CSR); wellbeing; growth rate; sustainable development and education